Estimation of the seasonal variation of particulate nitrate and sensitivity to the emission changes in the greater Seoul area - Lee, Sihye; Ghim, Young Sung; Kim, Yong Pyo; Kim, Jin Young (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
Seasonal variation of fine particulate nitrate and sensitivity of fine particle mass concentration to the emission changes of VOCs and NOx were estimated in the greater Seoul area. SBOX, a photochemical box model was used to obtain the total nitric acid (HNO3T) concentration, and SCAPE2, a gas/particle equilibrium model was used to determine the partitioning of nitric acid/nitrate and particulate water content. Most HNO3T existed as nitrate except in summer (similar to 60%) since there was enough ammonia to form particulate ammonium nitrate. In summer, high temperature was favorable to gaseous nitric acid. Also, because of average relative humidity (RH) higher than the deliquescence points of most salts, water content in summer was higher than those in other seasons by a factor of two. For all seasons, fine particle mass concentration (the sum of ion concentrations and water content) increased until considerable amount of NO, emissions was reduced. This phenomenon is a typical example of the so-called 'NOx disbenefits' that has been discussed in relation to the abatement of ozone pollution. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: VOLATILE ORGANIC-COMPOUNDS; GAS-AEROSOL EQUILIBRIUM; OZONE; POLLUTANTS; KOREA; SO2